ANALISIS PERAN "STEEMIANS" DALAM KOMUNITAS STEEMIT INDONESIA (KSI) BARSELA TERHADAP LITERASI POSITIF DI ACEH - Putri Maulina (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
The phenomenon of social media blogging Steemit over the last two years become a new trend in Indonesian society, especially in Aceh. Social media Steemit offers the latest system different from other social media with an emphasis on a blockchain system that rewards steem of dollars to its users. The outbreak of the use of Steemit media has led to the creation of communities within the community, known as the Indonesian Steemit Community (KSI), and one of them is in West Aceh called KSI Barsela. Steemit users who are members of this community then known as Steemian. Through this community of Steemian interaction to facilitate the achievement of reward in Steemit. In this case, communication becomes the main thing required in social interaction, one of which is role communication. The purpose of this study is to see how the role of communication performed by Steemian Barsela in the community. With the theory approach used is Role Theory to see three aspects: role expectation, role demands, and role skills. While the type of research is qualitative descriptive, with the method of observation and interview. The results of research on three aspects of the role illustrate that every Steemian in the community should promote effective forms of group communication in behaving and interacting with other Steemians.